Productivity and impact assessment of natural products chemistry research carried out in Sri Lanka - Yapa, Champa Geethika (Faculty of Science, University of Colombo, 2005)
This thesis consists of an account of the research findings of Sri Lankan natural products chemistry researchers from 1992 to 2002 and an analysis of the productivity and impact of natural products research carried out in Sri Lanka from 1975 to 2002. The first part consists of the analysis of scientific findings of natural products chemistry research carried out in Sri Lanka and the results of these studies. This aspect was done by reviewing the published information in peer reviewed local and international journals from 1992 - 2002. The second part is a bibliometric analysis carried out using the electronic database, the Science Citation Index Expanded (SCIE). During the course of this study, five Universities (University of Peradeniya, University of Sri Jayawardenepura, University of Colombo, University of Kelaniya and University of Ruhuna) and three Research Institutes (Medical Research Institute, Institute of Fundamental Studies and Industrial Technology Institute) were identified to be predominantly engaged in research in natural products chemistry. The important research findings in natural products chemistry for the period 1992- 2002, revealed that during the ten year period, a substantial and significant amount of work has been done by Sri Lankan natural products chemistry researchers who had investigated over 280 plant and animal species and over 60 species of lower plants, bacteria, fungi and sponges. However, although very important discoveries have been made by these researchers during the course of their investigations, most of these research results have not progressed into any products of commercial value. Further, despite of the rich biodiversity and many research groups working on natural products i research in Sri Lanka, the research work has given rise only to compounds which